DONGENG NUSANTARA SEBAGAI WAHANA MEMATANGKAN EMOSI ANAK DALAM BERCERITA - Anditasari, Restining (Universitas Negeri Surabaya, 2016)
In the story telling activity, it is often encountered many children that are intelligent and brilliant performance cannot process their emotions, so that their understanding of a story that should be channeled properly through emotional intelligence are not formed. In the process of finalizing the EI of students, the role of teachers is necessary. Teachers can use fairy tales as one literary work that can be used to develop EI of students. Fairytale has the potential to contribute to the emotional development of students. This is due to the involvement of all the senses when the students are listen/read a fairy tale. In addition, the fairy tale is effectively used in order to instill the values and ethics, including empathy and sympathy learners. The usage purpose of archipelago fairytale in storytelling is to help students cultivate EI, so it can provide a positive influence on the various actions taken by the student. The content of this article is about (1) the role of teachers in telling a story, (2) the emotional development of students, (3) storytelling as a stimulation to the EI of the students, and (4) the characteristics of fairytale archipelago right to ripen the EI of students